Moral and Psychological State of the Student’s Personality During End-of-Term Exams - AKHMEDOVA, Elmira M.; PETROVA, Nina F.; PASHINA, Svetlana A.; UVAROVA, Natalya N.; DUDAEV, Genaz S.-H. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article presents key aspects of the moral and psychological state of the student’s personality, as well as examines the characteristics of age and levels of anxiety as factors that affect the moral and psychological state of the students. Throughout the study, it is concluded that these categories, in addition to adaptation to new conditions, are determining factors for the moral and psychological affection of the student’s personality. RESUMEN El artículo presenta aspectos clave del estado moral y psicológico de la personalidad del estudiante, así como también, examina las características de edad, niveles de ansiedad como factores que afectan el estado moral y psicológico de los estudiantes. A lo largo del estudio, se concluye que estas categorías, además de la adaptación a las nuevas condiciones, son determinantes para la afección moral y psicológica de la personalidad del alumno.